2009
DOI: 10.3144/expresspolymlett.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi analysis of shrinkage and warpage of injection-moulded polypropylene/multiwall carbon nanotubes nanocomposites

Abstract: Abstract. This paper focuses on the effect of multi-walled carbon nanotube (MWNT) addition on shrinkage and warpage properties of polypropylene (PP) injection mouldings before and after annealing. A Taguchi design of experiments has been implemented to highlight the influence and optimise processing conditions such as injection flow rate, holding pressure, back pressure and screw speed. The addition of 2 wt% of carbon nanotubes into PP significantly reduces the shrinkage and warpage of injection-moulded parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…The application of PP in various industrial sectors can be further expanded once its mechanical performances have been highly upgraded. Therefore, PP has been a popular matrix used in association with all kinds of nanofillers such as carbon nanotubes (CNTs) [8][9][10][11][12], layered silicates (clays such as montmorillonite (MMT) etc.,) [13][14][15] and nanoparticles such as silica, graphite and calcium carbonate [16][17][18][19], even though the nanofiller dispersion is challenging in that case and often remains an issue. Halloysite nanotubes (HNTs) have recently become the subject of research attention as a new type of additive for enhancing the mechanical, thermal and fire-retardant performance of polymers [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The application of PP in various industrial sectors can be further expanded once its mechanical performances have been highly upgraded. Therefore, PP has been a popular matrix used in association with all kinds of nanofillers such as carbon nanotubes (CNTs) [8][9][10][11][12], layered silicates (clays such as montmorillonite (MMT) etc.,) [13][14][15] and nanoparticles such as silica, graphite and calcium carbonate [16][17][18][19], even though the nanofiller dispersion is challenging in that case and often remains an issue. Halloysite nanotubes (HNTs) have recently become the subject of research attention as a new type of additive for enhancing the mechanical, thermal and fire-retardant performance of polymers [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Compounding and processing of such materials have to be carefully mastered, as the final properties of the obtained nanocomposites strongly depend on the nanofillers dispersion state and the microstructural changes locally induced upon nanoparticle addition. Polyamide matrices are often used to develop such nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted the design of experiments with a total of 36 experiments in which the optimal setting combination was identified as 93 in/min for feed rate, 100 V for voltage and 63 A for amperage. Prashantha et al (2009) in their research found that the addition of 2 wt% of carbon nanotubes into polypropylene (PP) significantly reduced the shrinkage and warpage of injection-moulded parts up to 48%. The method employed was the Taguchi approach to study the effects of process parameters on the warpage and shrinkage of injection-moulded parts.…”
Section: Literature Reviewmentioning
confidence: 99%